Natural rubber truck tyre compounds for improved wear performance - Baker C S L; Wallace I R (Journal of Natural Rubber Research, 1986)
The trend to pre-cure treads has reduced the need to use NR in heavy-duty truck tyre retreading. Thus, NR compounds have had to complete solely on a tread life basis where, under normal highway conditions with relatively low severity, SBR/BR compounds would probably be found superior owing to the reversion characteristics of NR. A high stearic acid semi-EV system has been developed for NR, whose abrasion resistance does not, as is usually observed, deteriorate on overcure. In fleet trials, 80/20 NR/BR treads based on this formulation were found to come close to a high mileage SBR/BR tread under low severity conditions, and surpass it under high severity conditions. Rig testing has also shown the new NR compound to have improved rolling resistance and lower running temperatures. In a second series of trials, NR dominant compounds with this new curing system and an increased proportion of BR were examined, and a formulation has been found which has a longer tread life than the synthetic control under low severity conditions.
Keywords: Natural rubber; Tyre